WORKERS’ RIGHTS, WELFARE, AND GOVERNANCE: INSIGHTS FROM A MANGO INDUSTRY IN THE PHILIPPINES - Noe John Joseph Endencio Sacramento (University of Muhammadiyah Malang, 2020)
Major concerns centered on the governance of the working sector stems from issues and challenges confronted in the protection of workers’ rights and welfare. This case study discusses the challenges faced by the workers in the Guimaras mango industry and the role of the local government in addressing the gaps in the protection of the workers’ rights and welfare. Findings from the 35 key informant interview with the workers show that there are major gaps concerning workers’ rights and welfare that still needs to address despite the efforts of the government to provide the necessary program, projects, and legislation for the industry. The local government has pursued public services on agricultural support and mechanisms for addressing some of the needs of the mango producers and local legislations on mango production, harvesting, and consumption to protect them and the industry. Major workers’ rights and welfare concerns are mainly on hazardous and dangerous work practices, the undependability of the mango industry as a primary source of income, low wage, and the unstable contractual-hiring of mango workers during the mango season— all have to undermine just to meet the supply needed as demanded by the market. To infer, the workers are essential key players of the mango industry; thus, their rights and welfare need to be appropriately protected. In addressing social justice, fairness, and equality, local governments, humanitarian groups, and helping organizations are encouraged to center their agenda on advancing the rights, interests, and welfare of the sector.